2008
DOI: 10.1007/s00330-008-1249-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of cartilage repair tissue of the patella and medial femoral condyle by using morphological MRI and biochemical zonal T2 mapping

Abstract: The objective of this study was to use advanced MR techniques to evaluate and compare cartilage repair tissue after matrix-associated autologous chondrocyte transplantation (MACT) in the patella and medial femoral condyle (MFC). Thirty-four patients treated with MACT underwent 3-T MRI of the knee. Patients were treated on either patella (n = 17) or MFC (n = 17) cartilage and were matched by age and postoperative interval. For morphological evaluation, the MR observation of cartilage repair tissue (MOCART) scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 42 publications
1
50
0
Order By: Relevance
“…In recent studies of knee cartilage repair tissue by Welsch et al (13,18), the authors reported a gradual recovery of cartilage T 2 zonal variation after surgery. Furthermore, the authors reported that differences between healthy cartilage and cartilage repair tissue were most obvious within the deep cartilage layer for both the PAT and the MFC (18).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In recent studies of knee cartilage repair tissue by Welsch et al (13,18), the authors reported a gradual recovery of cartilage T 2 zonal variation after surgery. Furthermore, the authors reported that differences between healthy cartilage and cartilage repair tissue were most obvious within the deep cartilage layer for both the PAT and the MFC (18).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the authors reported that differences between healthy cartilage and cartilage repair tissue were most obvious within the deep cartilage layer for both the PAT and the MFC (18).…”
Section: Discussionmentioning
confidence: 99%
“…They reported an increase of T2 values over the condyle compared to the patella repair tissue. They conclude that differential maturation of the repair tissue depends on its environment [51].…”
Section: Clinical Application Of T2 Mapping In Cartilage Repair Surgerymentioning
confidence: 99%
“…1.5 T scan able to perform a T2 mapping. Sequences for global cartilage assessment and qualitative measures of the cartilage morphology have been validated both in vitro and in vivo and are available for clinical use through 1,5T and 3T scanners [32,[43][44][45][46][47][48].…”
Section: Imagementioning
confidence: 99%
“…Small changes in collagen hydration and organization lead to cartilage degradation and OA early findings may be evident through T2 mapping before any standard procedure such as radiological tests [30][31][32].…”
Section: Introductionmentioning
confidence: 99%